Measuring the inequalities in healthcare resource in facility and workforce: A longitudinal study in China - Dong, Enhong; Sun, Xiaoting; Xu, Ting; Zhang, Shixiang; Wang, Tao; Zhang, Lufa; Gao, Weimin (Frontiers in Public Health, 2023)
Objective: The study aimed to measure time trends of inequalities in the geographical distribution of health facility and workforce in Shanghai from 2010 to 2016, and using a spatial autocorrelation analysisi method to detect precisely the priority areas for optimizing health resource reallocation in metropolises like Shanghai in developing countries. Methods: The study used secondary data from Shanghai health Statistical Yearbook and the Shanghai Statistical Yearbook from 2011 to 2017. Five indicators on health resources, including health institutions, beds, technicians, doctors and nurses were employed to quantitatively measure the healthcare resource in Shanghai. The Theil index and Gini coefficient were applied to assess the global inequalities in the geographic distribution of these resources in Shanghai. Global and local spatial autocorrelation was performed using global Moran’s index and the local Moran’s index to illustrate the spatial changing patterns and identify the priority areas for two types of healthcare resource allocation. Results: Shanghai’s healthcare resources showed decreasing trends of inequalities at large from 2010 to 2016. However, there still existed an unchanged over-concentration distribution in healthcare facility and workforce density among districts in Shanghai,especially for doctors at the municipal level and facility allocation at the rural level. Through spatial autocorrelation analysis it was found that there exhibited a significant spatial autocorrelation in the density distribution of all resources and some identified priority areas were detected for resources re-allocation policies planning. Conclusion: The study identified the existence of inequality of some healthcare resources allocation in Shanghai. Hence, more detailed area-specific healthcare resource planning and allocation policies are required to balance the health workforce distribution at municipal level and institution distribution at rural level, and certain geographical areas (low–low and low–high cluster areas) should be foucused on and full considered across all the policies and regional cooperation to ensure health equality for municipal cities like Shanghai in developing countries.